Formulation and Antibacterial Activity Testing of Face Mist Containing Binahong Leaf Extract (Anredera cordifolia L.) against Propionibacterium acnes - Wattiheluw, Muhammad Hasan; Nabila, Mega Aulia (Journal of Local Therapy, 2026)
Acne is one of the common skin problems and is often caused by the bacteria Propionibacterium acnes. Acne treatment with antibiotics can cause side effects, including bacterial resistance. Therefore, this study aims to formulate and evaluate the antibacterial activity of a face mist preparation containing binahong leaf extract (Anredera cordifolia), which is known to have natural antibacterial properties. The research method includes extraction of binahong leaves using the maceration method with 70% ethanol, face mist formulation with various extract concentrations (1%, 2%, and 3%), and evaluation of its physical properties and antibacterial activity using the disc diffusion method. The results of the physical property test showed that all formulations had a pH within a safe range for the skin (4.5-6.5), good homogeneity, and optimal spray spread. The antibacterial activity test showed that face mist with an extract concentration of 2% had the highest inhibitory power against P. acnes with an average inhibition zone of 19.83 mm, classified as strong. This, binahong leaf extract has the potential as an active ingredient in face mist preparations to treat acne.